2011
DOI: 10.1007/s10509-011-0907-3
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of ion acoustic shock waves in non-Maxwellian plasmas with (G′/G)-expansion method

Abstract: Korteweg-de-Vries-Burger (K-dVB) equation is derived for ion acoustic shock waves in electron-positronion plasmas. Electrons and positrons are considered superthermal and are effectively modeled by a kappa distribution in which ions are as cold fluid. The analytical traveling wave solutions of the K-dVB equation investigated, through the (G /G)-expansion method. These traveling wave solutions are expressed by hyperbolic function, trigonometric functions are rational functions. When the parameters are taken spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The authors explained the fact that power law tails are a consequence of distant particle energization processes. Many researchers have discussed the nonlinear phenomena in plasmas in the presence of electrons, obeying kappa distribution and showed that the characteristics of the waves modifies, in the presence of superthermality parameter κ [57][58]. El-Awady et al [59] studied the ion acoustic solitons in a multi component plasma with kappa distributed particles.…”
Section: Introductionmentioning
confidence: 99%
“…The authors explained the fact that power law tails are a consequence of distant particle energization processes. Many researchers have discussed the nonlinear phenomena in plasmas in the presence of electrons, obeying kappa distribution and showed that the characteristics of the waves modifies, in the presence of superthermality parameter κ [57][58]. El-Awady et al [59] studied the ion acoustic solitons in a multi component plasma with kappa distributed particles.…”
Section: Introductionmentioning
confidence: 99%
“…32 It is observed that an increasing positron concentration decreases the amplitude of the waves. The characteristics of ion-acoustic shock waves in electron-positron-ion plasma were investigated in 33 where electrons and positrons were modeled by kappa distribution function. It is seen that the amplitude of ion-acoustic shock waves decreases as the positron density and electron temperature increases.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that the amplitude of ion-acoustic shock waves decreases as the positron density and electron temperature increases. 33 In addition, Shah et al 34 have investigated the effect of positron beam on the ion-acoustic shock wave in a plasma consisting of inertial ions and superthermal electrons and the positron beam. They have derived the spectral index of the superthermal electrons, and concentration of impinging positron beam have significant effects on both the amplitude and steepness of the ion-acoustic shock wave.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the propagation of shock waves in superthermal plasmas was studied by some researchers. [36][37][38][39] However, most theoretical investigations, some are cited above, are restricted to propagation of non-linear waves (solitons or shocks) in collisionless plasmas. The aim of this article is to investigate the non-linear dynamics of IAWs in a dissipative EPI plasma, whereas the dissipative effect in our plasma model was considered to be due to the collision between ions and neutral particles.…”
Section: Introductionmentioning
confidence: 99%